Effect of oral baclofen on spasticity poststroke: responders versus non-responders. Issue 6 (18th August 2018) - Mizuno, Shiho; Takeda, Kotaro; Maeshima, Shinichiro; Shigeru, Sonoda
ABSTRACT: Objective To assess quantitatively the efficacy of oral baclofen for spasticity poststroke. Methods The participants were 29 persons poststroke with increased resistance to passive ankle dorsiflexion and ankle clonus on clinical assessment. Baclofen was administered at 20 mg/day for 1 week. The ankle joint was passively dorsiflexed at either 5°/s (slow stretch) or 90°/s (fast stretch) by a custom-built device. The ankle joint angle and resistive torque were measured during the ramp-and-hold stretch, with gastrocnemius electromyogram. The main outcome measures were the numbers of ankle clonus during hold, and the torques at 10° of ankle dorsiflexion in slow stretch (T-slow) and fast stretch (T-fast). Moreover, the velocity-dependent torque (ΔT = T-fast − T-slow) was compared between before and after oral baclofen. Results The numbers of ankle clonus, T-slow, T-fast, and ΔT for all participants did not exhibit significant differences between before and after baclofen administration. However, reduction in the number of ankle clonus of five or more was accompanied with a reduction in ΔT (4.0 ± 1.8 Nm) in three participants (the responders). Conclusion Although the responder rate was low, some participants responded to oral baclofen. Thus, a short-term trial of oral baclofen, and quantitative and electrophysiological assessments of muscle tone and ankle clonus are recommended.